2019
DOI: 10.1111/bcp.13962
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic exposure of metformin in patients with non‐alcoholic fatty liver disease

Abstract: Aims: Metformin is first-line treatment of type 2 diabetes mellitus and reduces cardiovascular events in patients with insulin resistance and type 2 diabetes. Target tissue for metformin action is thought to be the liver, where metformin distribution depends on facilitated transport by polyspecific transmembrane organic cation transporters (OCTs). Non-alcoholic fatty liver disease (NAFLD) is the most common liver disease in the western world with strong associations to insulin resistance and the metabolic synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 53 publications
2
17
0
2
Order By: Relevance
“…The observed lack of a difference in OCT1 abundance in normal and NASH liver tissues ( Table ; Figure ) is in agreement with the limited variability in morphine PK in NASH . This can be further corroborated by a radiolabeled ( 11 C‐metformin) positron emission tomography (PET)–computed tomography imaging study, which demonstrated similar hepatic exposure to metformin among patients with simple steatosis and with NASH . On the other hand, the plasma exposure of morphine glucuronides, M3G and M6G, increased in NASH subjects in the absence of change in parent PK .…”
Section: Discussionsupporting
confidence: 70%
“…The observed lack of a difference in OCT1 abundance in normal and NASH liver tissues ( Table ; Figure ) is in agreement with the limited variability in morphine PK in NASH . This can be further corroborated by a radiolabeled ( 11 C‐metformin) positron emission tomography (PET)–computed tomography imaging study, which demonstrated similar hepatic exposure to metformin among patients with simple steatosis and with NASH . On the other hand, the plasma exposure of morphine glucuronides, M3G and M6G, increased in NASH subjects in the absence of change in parent PK .…”
Section: Discussionsupporting
confidence: 70%
“…Although it can be metabolized in the intestine, 23 morphine is taken up primarily into the liver by organic cation transporter (OCT) 1, where it is rapidly metabolized mainly by UGT2B7 to its major metabolites morphine-3-glucuronide (M3G) and morphine-6-glucuronide (M6G). 20,24,25 OCT1 activity and UGT2B7 mRNA levels do not appear to be altered in NASH, 8,11,18 which is consistent with similar morphine PK profiles in healthy subjects and patients with NASH. 14 M3G formed in the liver undergoes excretion into bile (canalicular efflux) via multidrug-resistance associated protein (MRP) 2 and basolateral efflux to the systemic circulation via MRP3.…”
Section: How Might This Change Clinical Pharma-cology or Translationasupporting
confidence: 75%
“…To date, transporter changes in NASH have been linked to altered PKs of acetaminophen glucuronide, morphine glucuronides, and the nuclear imaging agent 99m Tc‐mebrofenin 13–16 . Conversely, NAFLD had no effect on apixaban, rosuvastatin, or metformin PKs 17,18 ; however, this may not be the case in patients with NASH.…”
mentioning
confidence: 99%
“…At present, there are no effective targeted drugs for the treatment of NAFLD, and treatment includes diet therapy and lifestyle adjustment, liver protection and lipid lowering, and insulin sensitization. 49,50 Astaxanthin has a wide range of effects, and may play an effective role in preventing the pathogenesis of NAFLD from many aspects. In 2007, Ikeuchi et al studied the effect of astaxanthin supplementation on obese mice fed a high fat diet.…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%